The Secret Role of microRNAs in Cancer Stem Cell Development and Potential Therapy: A Notch-Pathway Approach - Prokopi, Marianna; Kousparou, Christina A.; Epenetos, Agamemnon A. (Frontiers in Oncology, 2015)
MicroRNAs (miRNAs) have been implicated in the development of some if not all cancer types and have been identified as attractive targets for prognosis, diagnosis and therapy of the disease. MiRNAs are a class of small non-coding RNAs (20-22 nucleotides in length) that bind imperfectly to the 3’-untranslated region of target mRNA regulating gene expression. Aberrantly expressed miRNAs in cancer, sometimes known as oncomiRNAs, have been shown to play a major role in oncogenesis, metastasis and drug resistance. Amplification of oncomiRNAs during cancer development correlates with the silencing of tumor suppressor genes; on the other hand, down-regulation of miRNAs has also been observed in cancer and cancer stem cells (CSCs). In both cases, miRNA regulation is inversely correlated with cancer progression. Growing evidence indicates that miRNAs are also involved in the metastatic process by either suppressing or promoting metastasis-related genes leading to the reduction or activation of cancer cell migration and invasion processes. In particular, circulating miRNAs (vesicle-encapsulated or non-encapsulated) have significant effects on tumorigenesis: membrane-particles, apoptotic bodies and exosomes have been described as providers of a cell-to-cell communication system transporting oncogenic miRNAs from tumors to neighboring cells and distant metastatic sites. It is hypothesized that MiRNAs control cancer development in a traditional manner, by regulating signaling pathways and factors. In addition, recent developments indicate a non-conventional mechanism of cancer regulation by stem cell reprogramming via a regulatory network consisting of miRNAs and Wnt/β-catenin, Notch, and Hedgehog signaling pathways, all of which are involved in controlling stem cell functions of CSCs. In this review, we focus on the role of miRNAs in the Notch pathway and how they regulate CSC self-renewal, differentiation and tumorigenesis by direct/indirect targeting of the Notch pathway.